A flexible hybrid CFD model for refrigerant mal-distribution among minichannels in parallel flow condensers. (July 2018) - You, Yonghua; Wu, Zhongda; Liu, Hanyu; Zhang, Anqi; Zeng, Xican; Shen, Xin
Highlights: A flexible hybrid CFD model with DEFINE Macros is built for parallel flow condenser. The proposed model could simulate fluid flow in condenser efficiently and accurately. Notable fluid mal-distributions are found among different tubes and minichannels. Physical mechanism of fluid mal-distribution is discussed with contours and vectors. Abstract: In the present work, a flexible hybrid CFD model is constructed for parallel flow condensers to compute their refrigerant mal-distributions, where the DEFINED Macros of ANSYS Fluent are utilized to embed the one-dimensional finite element analysis of the heat transfer and flow resistance of refrigerant flowing through flat tubes. The parallel flow condenser in the literature is simulated with current hybrid model, and the comparison between the numerical and experimental performances is conducted for validation. Besides, the refrigerant flowrates in different flat tubes and minichannels are predicted, and the physical mechanism of fluid mal-distribution is discussed based on contours and vectors. The current investigation demonstrates that the proposed hybrid model could simulate the refrigerant flow in parallel flow condensers efficiently and its prediction has a reasonable precision. Besides, notable mal-distributions among different flat tubes and different minichannels of same flat tube are observed in the 1st tube pass. The tube flowrates in the rest passes are relatively uniform, while the mal-distribution among different minichannels of same tube could be more notable, with the maximal relative deviation about 15.6%. The current numerical model could be referred for the optimal design of heat exchangers.